Control System for Project Management in a Construction Sector Company through the Earned Value Technique in the Caribbean (2022)
The present research work generates a solution to some inconveniences presented in an organization that executes construction projects, which has presented problems of delays in the works, cost overruns in the activities and reduction of the scope of the projects, for this reason it is carried out an analysis of the bibliography related to project management systems based on the earned value methodology and through documentary observation. Through an information collection tool, a diagnosis of the object of study was made, and it was extended to the construction sector of the Colombian Atlantic Coast with the objective of having regional trends. With the analysis of the results obtained, a project management system was proposed based on some of the organizational strengths that the company has. The design and implementation of this system are intended to improve the success of projects in terms of cost, duration a nd scope. © 2022 Latin American and Caribbean Consortium of Engineering Institutions. All rights reserved.